Passionately inclusive : towards participation and friendship in sport. Festschrift für Gudrun Doll-Tepper - Dumon, Detlef; Hofmann, Annette R.; Diketmüller, Rosa; Koenen, Katrin; Bailey, Richard; Zinkler, Constanze; Doll-Tepper, G. (Gudrun), 1947- (Waxmann, 2017)
On the occasion of Gudrun Doll-Tepper's birthday, we are looking back at exciting developments that have evolved over the past decades in sport and physical education. Despite all the challenges these global phenomena are facing, we can also observe fascinating changes, especially with regard to participation opportunities for girls and women as well as for persons with a disability in sport, physical education and physical activity. The contributing authors - leaders, experts, colleagues and friends of Gudrun Doll-Tepper - are providing an exceptional insight into this historical progress. Gudrun Doll-Tepper is recognised as one of the leaders in the activities that led to these changes - on the policy level, in sport practice and in the research and teaching remit of academia, especially in adapted physical activity and physical education. Her unique capacity for networking across sectors and disciplines, on local, national and global level, is exemplary for many of us. We understand that change requires a vision, confidence, strategy, stamina - and team work. In her long-standing career as a leader of various organisations, committees and commissions, as Honorary President of the International Council of Sport Science and Physical Education, as Vice President of the German Olympic Sports Confederation and as a university professor, Gudrun Doll-Tepper continues to inspire us.